Transgenic pigs expressing near infrared fluorescent protein—A novel tool for noninvasive imaging of islet xenotransplants. (21st December 2021) - Kemter, Elisabeth; Citro, Antonio; Wolf‐van Buerck, Lelia; Qiu, Yi; Böttcher, Anika; Policardi, Martina; Pellegrini, Silvia; Valla, Libera; Alunni‐Fabbroni, Marianna; Kobolák, Julianna; Kessler, Barbara; Kurome, Mayuko; et al.
Abstract: Background: Islet xenotransplantation is a promising concept for beta‐cell replacement therapy. Reporter genes for noninvasive monitoring of islet engraftment, graft mass changes, long‐term survival, and graft failure support the optimization of transplantation strategies. Near‐infrared fluorescent protein (iRFP) is ideal for fluorescence imaging (FI) in tissue, but also for multispectral optoacoustic tomography (MSOT) with an even higher imaging depth. Therefore, we generated reporter pigs ubiquitously expressing iRFP. Methods: CAG‐iRPF720 transgenic reporter pigs were generated by somatic cell nuclear transfer from FACS‐selected stable transfected donor cells. Neonatal pig islets (NPIs) were transplanted into streptozotocin‐diabetic immunodeficient NOD‐ scid IL2Rg null (NSG) mice. FI and MSOT were performed to visualize different numbers of NPIs and to evaluate associations between signal intensity and glycemia. MSOT was also tested in a large animal model. Results: CAG‐iRFP transgenic NPIs were functionally equivalent with wild‐type NPIs. Four weeks after transplantation under the kidney capsule, FI revealed a twofold higher signal for 4000‐NPI compared to 1000‐NPI grafts. Ten weeks after transplantation, the fluorescence intensity of the 4000‐NPI graft was inversely correlated with glycemia. After intramuscular transplantation into diabetic NSG mice, MSOT revealed clear dose‐dependent signals for grafts of 750, 1500, and 3000 NPIs. Dose‐dependent MSOT signals were also revealed in a pig model, with stronger signals after subcutaneous (depth ∼6 mm) than after submuscular (depth ∼15 mm) placement of the NPIs. Conclusions: Islets from CAG‐iRFP transgenic pigs are fully functional and accessible to long‐term monitoring by state‐of‐the‐art imaging modalities. The novel reporter pigs will support the development and preclinical testing of novel matrices and engraftment strategies for porcine xeno‐islets.